Shifting to Trauma-Informed Care in Inpatient Psychiatry: A Case Study of an Individual with Dissociative PTSD Undergoing EMDR Therapy - Winkler, Olga; Burback, Lisa; Greenshaw, Andrew J.; Jin, Jonathan (Case Reports in Psychiatry, 2023)
Caring for patients with personality disorders can be challenging due to risks associated with suicidal ideation, homicidal threats, splitting, and acting out with problematic behavior in psychiatric inpatient units. Limited resources on inpatient units further add to the stress and burden on staff. This case summarizes how trauma-informed care was implemented in an inpatient setting to produce marked improvement in a patient’s treatment outcomes as well as better staff engagement and satisfaction. This culture change in the approach to care was not an easy process, as effortful planning and resources were required for key elements such as ongoing coaching, education, and regular staff debriefings. This case report signals the need for service providers to enable health systems to examine rules and exceptions from a cultural perspective of considering equity, diversity, and inclusion (EDI)—to allow openness to rational exceptions, even if they are unconventional.